Knowledge and practices on childhood anaemia, thalassaemia and iron deficiency among mothers of children aged between 6 and 59 months in a suburban area of Sri Lanka - Ruwan Samararathna; A. V. C. Gunaratne; Sachith Mettananda (BMC, 2022)
Abstract Background Childhood anaemia is one of the most common public health problems worldwide. Here, we aim to describe the knowledge and practices on childhood anaemia, thalassaemia and iron deficiency among mothers of children aged between 6 and 59 months in a suburban district of Sri Lanka. Methods We performed a cross-sectional survey in the Gampaha District of Sri Lanka from December 2020 to February 2021. One well-baby clinic each from four Medical Officer of Health areas in the district was selected using stratified random sampling. Mothers of all children aged between 6 and 59 months attending well-baby clinics were recruited until the sample size was achieved. Data were collected using a self-administered questionnaire and analysed using logistic regression. Results A total of 392 mothers were recruited; 53% of their children were males. Only 33% of mothers had an accurate understanding of anaemia, while 71% and 28%, respectively, could name at least one symptom and two causes of anaemia; 12% could not name a single food rich in iron. Only 13% of mothers knew that thalassaemia is a cause of anaemia, and 14% had been screened for thalassaemia. Logistic regression analysis that examined for factors associated with higher knowledge of anaemia revealed that an accurate understanding of anaemia was associated with maternal age over 30 years (p < 0.05) and maternal education level beyond grade ten (p < 0.001). In contrast, higher knowledge of symptoms of anaemia was associated with maternal employment (p < 0.01). Conclusions The knowledge of anaemia and awareness of thalassaemia among mothers was poor. Very few mothers were aware of iron-rich food and feed it to their children. Despite being located in a thalassaemia-endemic region, very few knew that thalassaemia is a cause of anaemia and have got themselves screened for thalassaemia.